Capacitive-Loaded High-Power Low-Loss 3.0 T Magnetic Resonance Imaging Radio Frequency Combiner Design and Integrated Application - Yingliang Li; Shouhua Luo (Applied Sciences)
For high-power magnetic resonance imaging (MRI) radio frequency (RF) combiners operating in the frequency range from 60 MHz to 300 MHz, the primary challenges lie in achieving high-power transmission capability while minimizing the insertion loss (IL), reducing the physical dimensions, and meeting application bandwidth requirements. This paper presents a high-performance RF power combiner based on capacitor-loaded microstrip technology for 3.0T MRI radio frequency power amplifier (RFPA) systems. The proposed combiner features low loss, high integration, and miniaturization, and it comprises multiple branches, each employing microstrip lines and capacitors in a series–parallel arrangement to achieve an impedance transformation of 50 Ω to 100 Ω. Each branch was designed through theoretical analysis and electromagnetic simulations to achieve a line length 30% shorter than λ/4, a 6.2 mm line width, and 0.08 dB IL at the 3.0T MRI operation frequency band. A two-way to one-way combiner was further designed using this branch structure to achieve 0.2 dB IL through simulation optimization. A four-way to one-way combiner was then constructed by cascading two-way combiners and optimized via ADS-HFSS software(ADS2014 HFSS19) co-simulation. The fabricated combiner module uses an FR4 substrate and achieves a 0.4 dB insertion loss, −25 dB return loss, and 25 dB port isolation at 128 MHz ± 1 MHz, with compact dimensions (320 × 200 × 10 mm). To ensure high power capability, thermal analysis was performed to confirm that the module’s power-handling capacity exceeded 8 kW, and experimental validation with the 8 kW 3.0T RFPA demonstrated a stable temperature rise of approximately 2 °C. In this study, the innovative single-branch topology and the RF high-power four-to-one combiner for 3.0T MRI systems were used, resolving the trade-offs between power-handling capability, insertion loss, structural compactness, and operating bandwidth in MRI power combiners. The combiner was successfully integrated into the 3.0T MRI RFPA system, reducing the overall dimensions of the RFPA system and simplifying its installation, thereby enabling high-quality imaging validation. This solution demonstrates the scalable potential of the design for other high-field MRI systems operating in the MHz range (from tens to hundreds of MHz), including in 1.5T and 7.0T MRI systems.